Regionally Distinct Immune and Metabolic Transcriptional Responses in the Bovine Small Intestine and Draining Lymph Nodes During a Subclinical Mycobacterium avium subsp. paratuberculosis Infection - Ibeagha-Awemu, Eveline M.; Bissonnette, Nathalie; Do, Duy N.; Dudemaine, Pier-Luc; Wang, Mengqi; Facciuolo, Antonio; Griebel, Philip (Frontiers in Immunology, 2021)
Mycobacterium avium subsp. paratuberculosis (MAP) is the causative infectious agent of Johne’s disease (JD), an incurable granulomatous enteritis affecting domestic livestock and other ruminants around the world. Chronic MAP infections usually begin in calves with MAP uptake by Peyer’s patches (PP) located in the jejunum (JE) and ileum (IL). Determining host responses at these intestinal sites can provide a more complete understanding of how MAP manipulates the local microenvironment to support its long-term survival. We selected naturally infected (MAPinf, n=4) and naive (MAPneg, n=3) cows and transcriptionally profiled the JE and IL regions of the small intestine and draining mesenteric lymph nodes (LN). Differentially expressed (DE) genes associated with MAP infection were identified in the IL (585), JE (218), jejunum lymph node (JELN) (205), and ileum lymph node (ILLN) (117). Three DE genes (CD14, LOC616364 and ENSBTAG00000027033) were common to all MAPinf versus MAPneg tissues. Functional enrichment analysis revealed immune/disease related biological processes gene ontology (GO) terms and pathways predominated in IL tissue, indicative of an activated immune response state. Enriched GO terms and pathways in JE revealed a distinct set of host responses from those detected in IL. Regional differences were also identified between the mesenteric LNs draining each intestinal site. More down-regulated genes (52%) and fewer immune/disease pathways (n=5) were found in the ILLN compared to a higher number of up-regulated DE genes (56%) and enriched immune/disease pathways (n=13) in the JELN. Immunohistochemical staining validated myeloid cell transcriptional changes with increased CD172-positive myeloid cells in IL and JE tissues and draining LNs of MAPinf versus MAPneg cows. Several genes, GO terms, and pathways related to metabolism were significantly DE in IL and JE, but to a lesser extent (comparatively fewer enriched metabolic GO terms and pathways) in JELN suggesting distinct regional metabolic changes in IL compared to JE and JELN in response to MAP infection. These unique tissue- and regional-specific differences provides novel insight into the dichotomy in host responses to MAP infection that occur throughout the small intestine and mesenteric LN of chronically MAP infected cows.